ESD with double-balloon endoluminal intervention platform versus standard ESD for management of colon polyps - Ismail, Mohamed Saleh; Bahdi, Firas; Mercado, Michael Oliver; Habazi, Randa; Alexander, Angel; Prabhu, Sahana; John, Sharon; Kovvali, Chandra; Othman, Mohamed O. (Endoscopy International Open, 2020)
Background and study aims Endoscopic submucosal dissection (ESD) with the double-balloon endoluminal intervention platform (DEIP) is a novel technique for removal of complex colon polyps (> 2 cm) or those located in anatomically difficult positions. DEIP helps create a therapeutic zone with improved visualization and stability, facilitating polyp removal. We aimed to compare the outcomes of DEIP with the conventional cap-assisted ESD (standard ESD) technique for colon polyp resection, in particular, the ability to complete the ESD procedure without resorting to hybrid ESD or piecemeal resection.Patients and methods This was a retrospective cohort of all patients who underwent colon ESD in a single large tertiary referral center between September 2016 and October 2019. Information was collected on patient demographics and study outcomes including procedure time, rates of en bloc and curative resection, operative and postoperative complications. All patients were followed up for 1 month after the procedure.Results 111 patients were included in the study (DEIP 60, standard ESD 51). There was no statistically significant difference between mean procedures time (± SD) in the two groups, mean (81.9 ± 35.4 min standard vs. 96.4 ± 42.2 min in DEIP). Mean polyp size (± SD) was similar between the two groups (7.6 ± 6.0 cm2 vs. 6.2 ± 5.5 cm2, P = .2). There were no significant differences in en bloc and curative resection rates or operative and postoperative complications between the two techniques.Conclusion Procedure time was similar using both techniques. However, DEIP enabled the entire procedure to be performed using the ESD technique without resorting to snare resection, which may affect the en bloc and curative resection rate. There were no significant differences in en bloc and curative resection rates between the two groups, probably due to the small sample size.